Pengaruh Model Pembelajaran Project Based Learning melalui Gerakan Literasi Sekolah terhadap Keterampilan Berbicara Siswa SMP Negeri 2 Sukamakmur Kabupaten Bogor - Zein, Shofa Farhana; Solihati, Nani; Amalia, Nur (LPPM Universitas PGRI Silampari Lubuklinggau, 2022)
This study aims to determine the influence of the project-based learning learning model of school iteration movement activities on the speaking skills of students of SMP Negeri 2 Sukamakmur, Bogor Regency. This research was carried out in the 2021/2022 school year, the second semester in May in class VIII. The method used in this study is an experimental method with the pretest-Posttest Control Group Design research design.. The sample technique used is Simple Random Sampling. This study used two classes, the control class and the experimental class. The instrument used in the form of a speaking test expresses opinions about the content of the reading, students are given readings in the form of short stories. The assessment indicator in the speaking skills test is that students must be able to indicate the intrinsic elements of short stories, namely themes, characters and characterization, settings, plots and mandates in front of the class. Liliefors test is used as a test for the normality of test results. The results showed that the results of testing the hypothesis using the t-test obtained tcount 6.03 > 2.00 = ttable at a significant level of 0.05 it turned out that tcount > ttable H0 was rejected and H1 was accepted. This means that there is a significant influence with the project based learning learning model applied in literacy movement activities on the speaking skills of students of SMP Negeri 2 Sukamakmur, Bogor Regency. The implication for learning Indonesian is that teachers can use project-based learning models in speaking skills in an effort to stimulate students so that students' brain abilities continue to develop and increase in acquiring lessons or in every teaching and learning activity.